Aktualisasi Pendidikan Islam (Suatu Upaya Membangun Paradigma Integral) - Suwadji (Tarbiyah Departement collaboration with AMCA, 2013)
Islamic education, basically considering the orientation of worldly and hereafter. Islamic education with universal concepts that need to be developed or actualized in a learning process that pertain to the development of Islamic education and the philosophical paradigm of integrative paradigm-universal, therefore this paper reveals the need for the actualization of the basic concepts of Islamic education as empowerment of Muslims.